Nepal Government uses CCAFS’ Tools for its Food Security Information System - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
CGIAR Research Programme on Climate Change (CCAFS) Regional Agriculture Forecasting Tool (CRAFT), was used by the World Food Program and the Government of Nepal to estimate pre-harvest wheat and paddy production during 2015-2020 for Nepal’s Food Security Monitoring System (NeKSAP). This tool not only supported food security monitoring during normal years but also during calamities (Earthquake-2015, COVID-2020) and federal restructuring (2017) of the Nepal Government.